Diagnosis and treatment of hep-2 cells contaminated with mycoplasma - Lopes, B. R.P. [UNESP]; Ribeiro, A. G. [UNESP]; Silva, T. F. [UNESP]; Barbosa, L. V. [UNESP]; Jesus, T. I. [UNESP]; Matsuda, B. K. [UNESP]; Costa, M. F. [UNESP]; Toledo, K. A. [UNESP] (FapUNIFESP (SciELO), 2021)
Contamination of primary and cell cultures by mycoplasmas is one of the main economic and biological pitfalls in basic research, diagnosis and manufacture of biotechnological products. It is a common issue which may be difficult to conduct surveillance on. Mycoplasma presence may affect several physiological parameters of the cell, besides being considered an important source of inaccurate and/or non-reproducible scientific results. Each cell type presents characteristical symptoms, mainly morphological, that indicate a contamination by mycoplasma. HEp-2 cells originate from carcinoma of the larynx and are, therefore, part of the respiratory tract, which is one of mycoplasma habitats. Despite the importance these cells in several biological research (evaluation of cell proliferation and migration, apoptosis, antiviral and antitumor compounds), the alterations induced by mycoplasma contamination in HEp-2 cells have not yet been described. Here, we describe the progressive morphological alterations in culture of HEp-2 cells infected with mycoplasma, as well as the-diagnosis of the infection and its treatment. Mycoplasma contamination described within this work led to cytoplasm elongation, cell-to-cell spacing, thin plasma membrane projections, cytoplasmic vacuoles, fusion with neighboring cells, and, finally, cell death. Contamination was detected by fluorescence imaging (DAPI) and PCR reactions. The cultures were treated with BM-Cyclin antibiotic to eliminate contamination. The data presented here will be of relevance to researchers whose investigations involve cell culture, especially respiratory and HEp-2 cells.
Diagnóstico e tratamento de células hep-2 contaminadas por micoplasma
Keywords: Cell culture; Contamination; HEp-2 cells; Mycoplasma; Treatment